Mester Trebing fra Hessen: Livet i glashytten Stenhule ved Silkeborg 1604-1610 - Linaa, Jette (Hikuin, 2010)
Meals and memories The consumption strategies of German glassmaker Liborius Trebing in the Danish glass workshop Stenhule around 1600 By Jette Linaa Extensive research has been carried out into Renaissance glass production and glass workshops, but the consumption patterns of the glass craftsmen are less well known. Even so, these patterns shed light upon an important aspect of the subject: the lifestyle, social status, identity and integration of the foreign glassmakers in their new surroundings. The glass workshop of Stenhule, near Silkeborg in Jutland, was founded by the German master glassmaker Liborius Trebing in 1604; production ceased in about 1610. Trebing came from Hessen In Germany He was employed by the King Frederik II in 1585 and he established several glass workshops in the area. The Stenhule workshop was excavated in 1964 and the many finds included a large amount of pottery. The latter is clearly very diverse and comprises vast amounts of decorated ceramics for representative purposes. The type-variation is extensive, encompassing Werra plates, highly decorated tankards and jugs from Raeren and Siegburg, Dutch red ware pots and Weser pots and plates. The local red ware cooking pots occur in a large variety of sizes, indicating that Trebing preferred the diverse and refined gastronomy of the Renaissance. The analysis of the pottery demonstrates that Liborius Trebing’s consumption had great similarities with that of Jutland’s nobility and bourgeoisie, as known from many high-status sites, and less in common with the patterns seen on local farms and in villages. Through a comparison with pottery from other early industrial sites inhabited by Germans in Sweden, the imported pottery, and especially the highly decorated stoneware tankards and jugs from Siegburg and Raeren, are linked to social strategies adopted among the craftsmen. This paper suggests that the use of representative vessels in Trebing’s glass workshop functioned both internally as a living, active medium, a marker of his memories and his identity in his new country, and externally, as a marker of Trebing’s elevated social position in his native Hessen, where he was regarded as a skilled and innovative craftsman. This strategy was probably directed towards both the Danish king and the king’s vassal at the castle in Silkeborg, who was Trebing’s superintendent. This article proposes that similar consumption strategies may be found relating to many foreign craftsmen who settled in Scandinavia during the 16th and 17th centuries.